Complete mitochondrial genomes of the Prototheca genus: comparative genomics and evolutionary insights - Daniel Wibberg; Zofia Bakuła; Iván García-Cunchillos; Jan Gawor; Robert Gromadka; Anna Karnkowska; Jacek Bielecki; Tomasz Jagielski (BMC Genomics)
Abstract Background Prototheca (Chlorophyta: Trebouxiophyceae) is a genus of non-photosynthetic microalgae that causes increasingly frequent infections in both humans and animals, collectively referred to as protothecosis The genetic landscape of the Prototheca algae has remained largely uncharted until recent advances in sequencing and genomics. In this study, a combination of Illumina and Oxford Nanopore technologies was employed for sequencing of 18 mitochondrial genomes, representing all currently recognized Prototheca species. Results The genomes differed in terms of size and GC content, ranging from 38 kbp to 68 kbp and from 25 to 30%, respectively. The gene content and gene order within the mitochondrial DNA exhibited specific characteristics. The gene content was conserved but showed variable number of hypothetical proteins and a clustering tendency for nad genes. Noteworthy, most genes were located on the clockwise strand, with type I introns, containing long open reading frames encoding homing endonucleases, suggesting a mechanism for intron mobility and genome plasticity. Comparative genomic analyses and phylogenetic classification across the 21 core genes showed a close relationship between the mitochondrial genomes, as evidenced by average nucleotide identity (ANI) and average amino acid identity (AAI), supportive for the current cytb gene-based taxonomy. The phylogenetic tree constructed from concatenated alignments of the core genes confirmed the presence of three distinct Prototheca clades, indicating the polyphyletic nature of the genus. Conclusions In conclusion, this work provides another important step toward elucidating the genetics of Prototheca algae, serving as a framework for future studies on the phylogeny and evolution of these peculiar microorganisms.